FACTORS THAT AFFECT THE UTILIZATION OF ELDERLY POSYANDU AT THE HEALTH CENTER FOR CARE OF BLANGKEJEREN CITY. GAYO LUES ACEH PROVINCE - Mas, Sukri; Anggraini, Indah; Nasution, Ramadhani Syafitri (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
The use of elderly posyandu plays an important role in improving the quality of life, but the level of use is still low. This study aims to analyze the factors that affect the use of elderly posyandu in the Working Area of the Blangkejeren City Care Health Center. The research method used a cross sectional design with a sample of 91 respondents selected through stratified random sampling from a population of 973 elderly people. Data were collected using a questionnaire in March–May 2025 and analyzed by chi-square test and logistic regression. The results showed that education (p<0.001), attitude (p=0.001), knowledge (p<0.001), family support (p=0.016), health worker support (p=0.016), and health service facilities (p<0.001) were related to the use of elderly posyandu, while age (p=0.010) and distance (p=0.139) were not related. The dominant variable was attitude (p=0.001; Exp(B)=7.276). It was concluded that increasing the use of elderly posyandu needs to pay attention to education, attitudes, and family support and health workers.